Porous bioceramic production using human teeth [İnsan di̇şi̇ kullanilarak gözenekli̇ bi̇yoserami̇k üreti̇mi̇] - (:unkn) unknown (My University, 2002)
Bioceramics like hydroxyapatite (HA) and bioglass are wideliy used in the treatment of bone defects in medicine and dentistry. When these materials can imitate the porous structure of bone and with improved load-resistance besides their biocompatibility, they can be accepted as an appropriate biomaterial. Because of the poor mechanical properties of HA, it is mixed with other materials in order to obtain a composite with high load-resistance. Bioglass is another suitable material in the production of a biocompatible composite. The purpose of this study is to explain the manufacturing process of bioceramics with controlled porosity by a simple method. Hydroxyapatite material used in derived from calcined human teeth. Sodium-free bioglass material is derived from reagent grade chemicals. Moist wood flour with a grain diameter of 100 μm is used as a filling material. Bioceramic powders are compacted using double action hydraulic press. These pressed specimens had dimensions of 10 mm in diameter and 5 mm height. Blanks were sintered in a furnace at various temperatures. A high degree of porosity was obtained in blanks produced from HA, bioglass and HA-bioglass composites. When porous structure was examined, it is seen that every pore in the meshwork is connected to other pores. With the manipulation of heat-process time and temperature, exact chemical phases can be produced as needed. This method seems to be simple and economic as desired structures can be produced by temperature and time control with heat treatment.
Keywords: Biocompatibility; Bioglass; Hydroxyapatite; Porosity